2012
DOI: 10.3892/mmr.2015.3558
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide inhibits breast cancer cell growth via microRNA-328/hERG pathway in MCF-7 cells

Abstract: Abstract. Arsenic trioxide (As 2 O 3 ) has been widely used in the treatment of acute promyelocytic leukemia and has been observed to exhibit therapeutic effects in various types of solid tumor. In a previous study by this group, it was shown that As 2 O 3 induces the apoptosis of MCF-7 breast cancer cells through inhibition of the human ether-à-go-go-related gene (hERG) channel. The present study was designed to further investigate the effect of As 2 O 3 on breast cancer cells and to examine the mechanism und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Studies have shown that ATO was an effective therapeutic agent in APL with 63.8 to 93% high remission rate and could prolong patients' survival rate (13). A number of studies also have revealed a pro-apoptotic activity of ATO in solid tumors, including breast cancer, gastric cancer, hepatocellular carcinomas and sarcoma (14)(15)(16)(17). Although ATO is able to improve the disease outcome, of note, ATO also introduces to common side effects such as gastrointestinal disorders, cough, fatigue, skin rash, myelosuppression and the most burden are the liver function failure and cardiac toxicity (18).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that ATO was an effective therapeutic agent in APL with 63.8 to 93% high remission rate and could prolong patients' survival rate (13). A number of studies also have revealed a pro-apoptotic activity of ATO in solid tumors, including breast cancer, gastric cancer, hepatocellular carcinomas and sarcoma (14)(15)(16)(17). Although ATO is able to improve the disease outcome, of note, ATO also introduces to common side effects such as gastrointestinal disorders, cough, fatigue, skin rash, myelosuppression and the most burden are the liver function failure and cardiac toxicity (18).…”
Section: Introductionmentioning
confidence: 99%
“…At low doses (0.01–1 μM), arsenic compounds increased proliferation of non‐tumorigenic MCF‐10A (As 2 O 3 ), and breast cancer MCF‐7 (As III ) cells . Conversely, at higher concentrations (∼5–10 μM), these compounds exerted apoptotic effects associated with accumulation of caspase enzymes, p21, growth arrest DNA‐damage‐inducible‐α GADD45 , and miR‐238 . These data pointed to chronic exposure as potentially important for transformation of normal breast epithelial cells, or growth of preneoplastic cells, as confirmed in prostate tissue in which As III triggered the transition to a steroid hormone‐independent phenotype .…”
Section: Resultsmentioning
confidence: 98%
“…There is emerging evidence that ion channels play a role in many, and potentially all cancers. Therapeutics against voltage gated potassium channels have been shown in vivo to improve prognosis for glioblastoma and breast cancer (Arcangeli and Becchetti, 2017; Pointer et al, 2017; Wang et al, 2015), and there are studies implicating specific sodium (Brisson et al, 2011; Roger et al, 2015) and calcium channels (Phan et al, 2017; Qu et al, 2014) in cancers. We present strong evidence that the KCNQ family of genes also play a significant and functional role in human gastrointestinal cancers.…”
Section: Discussionmentioning
confidence: 99%